Approximation Properties of Bivariate Extension of q-Stancu-Kantorovich Operators - Acu, Ana Maria; Sofonea, Daniel Florin (Journal of Advances in Applied & Computational Mathematics, 2015)
In this paper we introduce a new q-Stancu-Kantorovich operators and we study some of their approximation properties. Furthermore, a Voronovskaja type theorem is also proven.